Pengembangan Pariwisata Dengan Pendekatan Community Based Tourism (CBT) Di Desa Wera, Kecamatan Pamona Puselemba, Kabupaten Poso - Kaliey, Ricky Yohanes; Eisenring, Deltri Dikwardi; Lutfi, Lutfi; Sarifuddin, Sarifuddin; Burhanuddin, Burhanuddin (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2025)
This research aims to formulate a sustainable tourism development strategy involving the community of Wera Village. The research employed a mixed-methods approach to understand the village's potential and tourist needs. The research results are outlined in four main strategies: (1) optimizing natural potential as the main attraction, (2) improving the quality and quantity of supporting tourism facilities, (3) utilizing digital technology for more effective promotion, and (4) empowering the community through training and active participation in management. Based on the research results, several strategic steps are recommended. First, the local government needs to allocate sufficient funds for the development of tourism infrastructure and facilities. Second, continuous training programs must be implemented to enhance the community's capacity in managing the tourism sector. Third, comprehensive regulations are needed to regulate tourism activities and protect the environment. Finally, increasing public awareness of the importance of environmental sustainability and culture, as well as their active participation in tourism management, is essential.